Multinational appraisal of the epidemiological distribution of opioid fatalities: a systematic review and meta-analysis - Onohuean, Hope; Oosthuizen, Frasia (Frontiers in Psychiatry, 2024)
The global or multinational scientific evidence on the distribution of opioid fatality is unknown. Hence, the current study collects epidemiological characteristics to shed light on the ongoing global/multinational opioid crisis and to promote the development of public health prevention/management strategies.Method: All documents were retrieved on PRISMA standards via electronic databases.Results: Among the 47 articles relevant to our studies, depicts a total population of 101 91, with a prevalence of fatal opioid overdose of 15 022 (14.74%). Fourteen studies report the gender; males 22125 (15.79%) and females 7235 (5.17%), the age distribution indicating age-group (18-34 years) 29272 (31.13%), and <18 years, 25316 (26.92) mostly impacted. Eighteen studies qualified for meta-analysis of the multinational prevalence of opioid fatalities, depicting an overall pool estimate proportion of 19.66%, 95% CI (0.13-0.29), with an I 2 =99.76% by random effect model, and Q statistic of (Q=7198.77, p<0.0001). The Egger test models of publication bias reveal an insubstantial level of bias (p = 0.015). The subgroup analysis indicates the study design (Cohort or Other), others have the highest prevalence estimate of 34.37%, CI (0.1600 0.5901), I 2 =97.04%, and sample size less-than 1000 shows the highest prevalence of 34.66%, CI (0.2039-0.5234), I 2 =97.82% compared to more than 1000 sample size with a prevalence of 12.28%, CI (0.0675-0.2131) I 2 =99.85%. The meta-regression indicates that the sample size (less-than or greater-than 1000), (P=0.0098; R 2 =3.83%) is significantly associated with the observed heterogeneity.